Early Psychosis and Trauma-Related Disorders: Clinical Practice Guidelines and Future Directions - Cragin, Casey A.; Straus, Martha B.; Blacker, Dawn; Tully, Laura M.; Niendam, Tara A. (Frontiers in Psychiatry, 2017)
Despite high rates of trauma-related disorders among individuals with early psychosis, no clinical practice guidelines for the treatment of comorbid early psychosis and trauma-related disorders exist to date. Indeed, the routine exclusion of individuals with past and current psychosis from participation in trauma research and practice has limited the accumulation of research that could support such clinical practice guidelines. While preliminary research evidence suggests that traditional, evidence-based treatments for trauma-related disorders can be safely and effectively employed to reduce symptoms of posttraumatic stress and chronic psychosis, it remains unclear whether such treatments are appropriate for individuals in the early stages of psychotic illness. Clinical experts (N = 118) representing 121 early psychosis programs across 28 states were surveyed using the expert consensus method. Forty-nine clinical experts responded and reached consensus on 46 of 49 expert consensus items related to the treatment of comorbid early psychosis and trauma-related disorders. Conjoint or family therapy and individual therapy were rated as treatment approaches of choice. Anxiety or stress management and psychoeducation were rated as treatment interventions of choice for addressing both trauma symptoms and psychotic symptoms. In addition, case management was rated as a treatment intervention of choice for addressing psychotic symptoms. No consensus was reached on expert consensus items regarding the appropriateness of a parallel treatment approach exposure interventions for addressing psychotic symptoms, or sensorimotor or movement interventions for addressing trauma symptoms. In areas where expert consensus exists and is supported by current research, preliminary clinical practice guidelines for the treatment of comorbid early psychosis and trauma-related disorders are offered. In areas where expert consensus does not exist, recommendations for future research are offered. The results of this study are intended to serve as a launching point for scientists and practitioners interested in advancing appropriate treatment for high-risk and underserved individuals with comorbid early psychosis and trauma-related disorders.